PENGARUH PENAMBAHAN DAUN MINT (Mentha piperita L.) DAN DAUN STEVIA (Stevia rebaudiana) TERHADAP KARAKTERISTIK SENSORI TEH CELUP DAUN KELOR (Moringa oleifera) - Murhadi, Murhadi; Eriska, Sovia; Nur, Muhammad; Rizal, Samsul (Jurusan Teknologi Hasil Pertanian, 2023)
This study aims to determine the effect of the addition of mint leaves and stevia leaves and their interactions on the sensory characteristics of Moringa leaf tea bags. This study was arranged in a complete randomized block design (CRBD) with two factors in 2 replications. The first factor was the concentration of mint leaves in this study, namely 0%, 2%, 4% and 6%. The second factor is the concentration of stevia leaves 0%, 2%, 4% and 6%. The data obtained were analyzed for variance and further analyzed with the Orthogonal Polynomial test at the 5% level. Moringa leaves, mint leaves and stevia leaves were dried at 50℃ for 20 hours. The three ingredients were ground in a blender, sieved, mixed according to treatment and put in 2 grams of tea bags. The best research results were obtained in the combination of 4% mint leaves and 4% stevia leaves with a taste value of 4.028, aroma of 3.983 (likes), color 4.000 (likes) and an overall acceptance score of 4.133 (likes) with a moisture content of 6.475% and an ash content of 7.246%.